Formulasi dan evaluasi bumbu instan nasi goreng yang diperkaya dengan bubuk lemi rajungan: Formulasi dan evaluasi bumbu instan nasi goreng yang diperkaya dengan bubuk lemi rajungan - Kusumaningrum, Indrati; Khotimah, Khusnul; Melati, Rahadina Praba; Afiah, Rahmania Nur; Affandi, Dian Rachmawanti (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2025)
Fried rice is one of Indonesia’s most popular dishes, creating a demand for practical seasoning alternatives such as instant seasoning made from crab lemi powder (LP), which provides a distinctive seafood flavor. This study aimed to evaluate the chemical, physical, and sensory characteristics of instant fried rice seasoning with varying proportions of LP and MSG. Four formulations (P0–P3) were developed using a completely randomized design. Chemical analyses included moisture, ash, protein, fat, carbohydrate, NaCl, and glutamate content. The physical analyses comprised measurements of bulk density, flowability, angle of repose, and color (L*, a*, and b*). Sensory evaluation was conducted using a hedonic test to assess color, aroma, taste, texture, and overall acceptability. Formulas P1 (34% LP : 3% MSG) and P2 (31% LP : 6% MSG) met the SNI standards for protein and fat content, with sodium levels significantly below the maximum limit, despite water content exceeds the standard (≤4%). Physically, all formulations showed densities of 0.71 to 0.74 g·mL⁻¹, flow times of 7.88 and 8.95 g·s⁻¹, and angles of repose below 30° (27.88°-28.61°), indicating excellent flowability and consistent color. Hedonic testing revealed that MSG addition had no significant impact on color, aroma, and texture but significantly improved taste and overall acceptability (p<0.05). Consequently, formulation P1, which had a lower MSG level, was identified as optimal, providing the best balance of physical stability, chemical quality, and sensory acceptability. This suggests its potential for development as a practical and safe instant fried rice seasoning product that is aligned with consumer preferences.